Assessing the feasibility of evaluating and delivering a physical activity intervention for pre-school children: a pilot randomised controlled trial. Issue 1 (December 2016) - Barber, Sally; Jackson, Cath; Hewitt, Catherine; Ainsworth, Hannah; Buckley, Hannah; Akhtar, Shaheen; Bingham, Daniel; Routen, Ash; Summerbell, Carolyn; Richardson, Gerry; Moore, Helen; Pickett, Kate; et al.
Abstract Background Few evidence-based physical activity interventions for pre-school children are available. This two-armed pilot cluster randomised controlled trial aimed to evaluate the feasibility of conducting a full-scale trial and of delivering an outdoor physical activity intervention for pre-school children. Methods School was the unit of randomisation, and follow-up occurred at 10 and 52 weeks. Trial feasibility was assessed by recruitment, retention and completion rates of primary (daily moderate-to-vigorous physical activity (MVPA)) and secondary (anthropometric, quality of life, self-efficacy) outcomes. Potential effectiveness was assessed for the primary outcome using a linear regression model comparing MVPA between trial arms adjusting for clustering by school. Feasibility of delivering the intervention was assessed by intervention fidelity and attendance. Semi-structured interviews with parents, intervention facilitators, and head teachers explored acceptability and capability to deliver the intervention as well as acceptability of the study design. Results Recruitment rates were 37 % of schools (n = 10 schools) and 48 % of pre-school children (n = 164 children). Retention of children to the trial at 52 weeks was 83.5 %. Thirty-nine percent of children had valid primary outcome accelerometer data at baseline and 52 weeks. Response rates for secondary outcome measures ranged from 52 to 88 % at 10 weeks and 59 to 80 % at 52 weeks. The mean difference in daily MVPA between trial arms at 52 weeks was 0.4, 95 % CI 16.3 to 17.0;p = 0.96. Fidelity of intervention implementation was 81 %. Intervention attendance was higher (82 %) during the summer initiation phase compared to autumn/spring initiation (50 %). Parents, facilitators and head teachers found the intervention acceptable and beneficial. Conclusions Recruitment and retention rates suggest a trial in this outdoor setting with this population was feasible but is weather sensitive. However, strategies to increase accelerometer wear-time would need to be implemented for reliable primary outcome data to be obtained. There was high implementation fidelity by facilitators, and the intervention was seen as acceptable and deliverable. However, attendance was low and preliminary data showed no evidence of intervention effectiveness. A revised intervention, building on the successful elements of this pilot alongside adapting implementation strategies to improve attendance, should therefore be considered. Trial registration Trial registry name and number: Current Controlled Trials, ISRCTN54165860 . Date of registration: 4 September 2012.